The Effect of Moringa Leaf Extract (Moringa oleifera) in Drinking Water on Broiler Chicken Carcass Production - Yunita Udju Riwu; N. G. A Mulyantini; Markus Sinlae; Ni Putu F Suryatni (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The research was carried out in the chicken house of the Faculty of Animal Husbandry, Marine and Fisheries, Nusa Cendana University, Kupang from April 7th 2023 to May 26th 2023. The aim of this research was to examine the effect of administering Moringa oleifera leaf extract in drinking water on broiler chicken carcass production. This research used 96 DOC broiler chickens of the CP 707 strain. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 6 replications, each replication consisting of 4 broiler chickens. The treatments given were P0= drinking water without moringa leaf extract (control), P1= 40 ml moringa leaf extract/l drinking water, P2= 80 ml moringa leaf extract/l drinking water, P3= 120 ml moringa leaf extract/l drinking water. The variables studied were final body weight, carcass percentage, non-carcass percentage and abdominal fat. The results of statistical analysis show that moringa leaf extract at levels of 0, 40, 80 and 120 ml/l of drinking water did not have a significant effect (P>0.05) on final body weight, percentage of carcass and non-carcass percentage of broiler chickens, but increased the percentage of abdominal fat significantly (P<0.05). Based on the research results, it can be concluded that the use of Moringa oleifera leaf in drinking water up to a level of 120ml/l drinking water can increase the percentage of abdominal fat but did not change the final body weight, carcass percentage and non-carcass percentage of broiler chickens.